Leads of COVID appropriate behaviour in ayurveda Samhita - C., Apekshya K.; Katti, Anand (International Journal of Advances in Medicine, 2022)
COVID-19 is global pandemic, indicating significant global spread of an infectious disease. COVID -19 pandemic has led to unprecedented and unanticipated challenges requiring collective actions and rules so, COVID appropriate behavior to fight the spread are being affectively led by central government and state government. There is need to reinforce the importance of preventive measures and practices in sustained manner to deal with the disease over the long run. Ayurveda is one world’s oldest holistic approach which deals with the prevention and management of the disease. A healthy education system should have codes of conduct for work place, society and family. Ayurveda has explained these codes of conduct under the tittle Sadvritta. Ayurveda emphasizes on social and personal behavior as they both affect mental and physical aspects of health. The codes explained in Ayurveda texts plays important role for the reduction of the highly spreading corona virus which in the present scenario can be related to the COVID appropriate behaviors which are critical to winning this fight against the deadly virus. In this article an attempt has been made for explaining the leads of COVID appropriate behavior in ayurveda Samhita.